The relationship between air pollution and company risk-taking: The moderating role of digital finance - Li, Xiuping; Yang, Ye (Frontiers in Environmental Science, 2022)
Air pollution, an influencing factor for decision-making behavior, is closely related to company risk-taking, which affects high-quality economic development. Based on a fixed effect model, using the panel data of non-financial listed companies from China’s A-share markets from 2011 to 2019, this study empirically analyzes the influence of air pollution on company risk-taking and the moderating role of digital finance. The benchmark regression results reveal that air pollution has a significantly negative impact on company risk-taking. Mechanism analysis reveals that digital finance that is not “green development-oriented” can strengthen such relationship. The results of the heterogeneity analysis demonstrate that the negative impact of air pollution on risk-taking is more significant within private companies and those located in the eastern and central regions. Digital finance impacts companies with strict financing constraints more significantly. This study provides a reference for reducing the negative impact of air pollution on high-quality economic development.